2017
DOI: 10.2166/wst.2017.096
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of water quality by UV/Vis spectrometry in the framework of treated wastewater reuse

Abstract: The aim of this study is to investigate the potential of ultraviolet/visible (UV/Vis) spectrometry as a complementary method for routine monitoring of reclaimed water production. Robustness of the models and compliance of their sensitivity with current quality limits are investigated. The following indicators are studied: total suspended solids (TSS), turbidity, chemical oxygen demand (COD) and nitrate. Partial least squares regression (PLSR) is used to find linear correlations between absorbances and indicato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 16 publications
1
20
0
Order By: Relevance
“…TSS and turbidity measurements were not logical between treatments. Previously, Carré et al (2017) demonstrated that a UV/VIS spectrometer is not reliable for measuring TSS or turbidity in low concentrations. Thus they calculated threshold values (TSS: 8 mg l -1 ; turbidity: 2 NTU), above of which spectrometer can be used to estimate TSS and turbidity values.…”
Section: Relative Water Renewal Ratementioning
confidence: 99%
“…TSS and turbidity measurements were not logical between treatments. Previously, Carré et al (2017) demonstrated that a UV/VIS spectrometer is not reliable for measuring TSS or turbidity in low concentrations. Thus they calculated threshold values (TSS: 8 mg l -1 ; turbidity: 2 NTU), above of which spectrometer can be used to estimate TSS and turbidity values.…”
Section: Relative Water Renewal Ratementioning
confidence: 99%
“…Many studies indicated that machine learning has potential for the analysis of single or multi-wavelength spectral data [ 10 , 20 , 21 , 22 , 23 ]. For instance, using UV absorbance spectrometry in the 250–300-nm region, Kim et al [ 24 ] used a multiple linear regression model to detect organic compounds in water.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, using UV absorbance spectrometry in the 250–300-nm region, Kim et al [ 24 ] used a multiple linear regression model to detect organic compounds in water. A partial least square (PLS) regression model was developed by Carré et al [ 21 ] to establish a relationship between spectral data and total suspended solids (TSSs), turbidity, and chemical oxygen demand (COD) in reclaimed water. Wolf et al [ 23 ] mapped the non-linear relationship between organic acid components and spectral data for online monitoring of anaerobic digestion processes in an industrial biogas plant.…”
Section: Introductionmentioning
confidence: 99%
“…Ideally, the concentration must be adjusted to absorb it so that the optimal measurement accuracy and accuracy are obtained. [12][13][14] Since the release of inorganic ions namely, Ca 2+ plays an important task in the effectiveness of dental materials, many studies have been carried out to measure the Ca 2+ ions released by different kinds of dental material. [15][16][17][18] Considering the newly developed material has not comprehensively evaluated particularly in its bioactivity by releasing Ca 2+ ions, our study aimed to evaluate the Ca 2+ release rate of the Ca(OH) 2 prototype from Indonesian limestone at different interval of time using an atomic spectrophotometer.…”
Section: Ca(oh)mentioning
confidence: 99%